FACTORS AFFECTING FOOD SECURITY IN RURAL AREAS IN YOGYAKARTA PROVINCE - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
The purpose of this research is to identify and analyze thefactors influencing the food security of rural society in the Province of Daerah Istimewa Yogyakarta (DIY). The location included several sub districts in the Regency of Sleman, Bantul, Kulon Progo, and Gunungkidul. Data utilized in this research were primary and secondary data. Primary data were compiled by survey and interviews. Secondary data were compiledfrom various publication sources. Data analyzed with multinomiallogit regression model. Factors influencing the food security of rural society in the Province of Daerah Istimewa Yogyakarta are based on three basic groups that are economy (income), socioculture (gender, kind of food, way of fertilization, technique of cultivation and knowledge of ecology) and ecology (land capability, land suitability, irrigation) ceteris paribus. The three factors cannot be separated in the equilibrium of eco-economy, eco-culture and ecology models. Keywords: food security, rural society, multinomiallogit, DIY.